2012
DOI: 10.1136/bmjqs-2011-000308
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding handover fumbles: a controlled trial of a structured handover tool versus traditional handover methods

Abstract: Standardisation of information transmitted during patient handovers through the use of a structured, web-based application led to consistent transfer of vital patient information and was associated with improved resident confidence and fewer perceived near-miss events on call.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 23 publications
0
47
0
3
Order By: Relevance
“…In 22% of the included studies, respondents reported increased or improved handoff content, 22,[29][30][31][32][33][34][35] and 22% of studies also reported high provider satisfaction with use of an electronic handoff system. [22][23][24][25][26][27]31,32 However, in 1 of these studies, 22.6% of respondents reported there was information they did not receive at handoff that would have helped them care for patients.…”
Section: Self-reported Measuresmentioning
confidence: 99%
“…In 22% of the included studies, respondents reported increased or improved handoff content, 22,[29][30][31][32][33][34][35] and 22% of studies also reported high provider satisfaction with use of an electronic handoff system. [22][23][24][25][26][27]31,32 However, in 1 of these studies, 22.6% of respondents reported there was information they did not receive at handoff that would have helped them care for patients.…”
Section: Self-reported Measuresmentioning
confidence: 99%
“…Hampir 1,3 juta kasus pada timbang terima pukul 21.00. Masing-masing kesalahan medis terjadi setiap tahunnya, dengan 48.000 observasi dilakukan pada hari yang berbeda untuk sampai 98.000 dari kasus tersebut mengakibatkan mendapatkan gambaran timbang terima dari 6 dokter full kematian pasien (4 (5). Komunikasi selama proses timbang terima yang khusus digunakan dalam proses tersebut, sehingga pasien merupakan periode kritis terhadap kontinuitas dan terjadi ketidakseragaman informasi yang disampaikan keberhasilan perawatan pasien (6).…”
Section: Pendahuluanunclassified
“…Hal tersebut akan rekaman proses timbang terima yang dapat dijadikan memperlama waktu penanganan pasien di UGD. (5). Tujuan dari timbang terima pasien adalah proses timbang terima selanjutnya dituangkan dalam terjadikomunikasi yang akuratdan dapat diandalkan bentuk lembar timbang terima.…”
Section: Pendahuluanunclassified
“…10 Web-based applications have been used to decrease variability. 11 22,23 A mechanism to electronically attach contingency plans for clinical deterioration, pending studies needing review, and tasks requiring completion (without incorporating these into the permanent medical record) further enhances the handoff communication. 14,22 Some of the content standardization may be possible with existing technology, but others may require novel features developed in conjunction with electronic medical record companies, information technology leaders, and hospital administrators; for instance, an organization may construct a sign-out template in a given format for use throughout the institution.…”
Section: Role Of Technologymentioning
confidence: 99%
“…In addition, maintaining a sign-out environment free of distractions and using available information technology tools can improve the efficiency and quality of information transfer. 5,10,11 As The Joint Commission, regulators, public and private payers, physician professional organizations, and hospitals attempt to curb medical errors, there is an intense focus on handoff communication. Studies have challenged the typical belief that handoffs between physicians are efficient and effective 12 and that handoffs between experienced providers are better than between trainees.…”
Section: Introductionmentioning
confidence: 99%